Transformasi Tata Kelola Maritim Indonesia Melalui Pendekatan Ideologi Pancasila: The Transformation of Indonesian Maritime Governance: A Pancasila-Based Approach - Maruf Kurniawan (Bhinneka Tunggal Ika: Pancasila Jurnal Internasional Berbahasa Indonesia, 2026)
Pancasila, as the state foundation and the way of life of the Indonesian people, holds fundamental relevance as an ethical compass in the implementation of national development, including in the maritime sector. The sea, as the living space of the Indonesian nation, possesses strategic value across economic, geopolitical, and sovereign dimensions. However, current maritime governance practices tend to be technocratic and pragmatic, failing to fully guarantee social justice for coastal communities or ensure ecological sustainability. This article aims to analyze the urgency of integrating Pancasila values into Indonesia’s maritime governance through a strategic synergy between the Agency for Pancasila Ideology Education (BPIP) and the Ministry of Marine Affairs and Fisheries (KKP). Utilizing a qualitative approach, this article outlines the implementative steps of the synergy between these two institutions, aiming to transform maritime governance so that it is not merely oriented toward economic growth, but also upholds the values of social justice, ecological sustainability, and national identity in accordance with the mandate of the state ideology.